2010
DOI: 10.1016/j.expneurol.2010.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the lateral cerebellar nucleus produces frequency-specific alterations in motor evoked potentials in the rat in vivo

Abstract: The cerebral cortex is tightly and reciprocally linked to the cerebellum and the ascending dentato-thalalmo-cortical pathway influences widespread cortical regions. Using a rodent model of middle cerebral artery stroke, we showed previously that chronic, 20 Hz stimulation of the contralateral lateral cerebellar nucleus (LCN) improved motor recovery, while 50 Hz stimulation did not. Using motor evoked potentials (MEP) elicited by intracortical microstimulation, we now show the effect of LCN stimulation on motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 52 publications
(67 reference statements)
2
43
0
Order By: Relevance
“…14 Invasive cerebellar stimulation has also been studied. Deep brain stimulation of the cerebello-thalamo-cortical pathway, specifically of the lateral cerebellar nucleus, 119 has been shown in preclinical rodent models to modulate cerebral cortex excitability 7 and improve postischemia motor recovery. 106 More recently, chronic cerebellar DBS demonstrated promotion of long-term potentiation, neuroplasticity, and reparative reorganization.…”
Section: Cerebellar Stimulationmentioning
confidence: 99%
“…14 Invasive cerebellar stimulation has also been studied. Deep brain stimulation of the cerebello-thalamo-cortical pathway, specifically of the lateral cerebellar nucleus, 119 has been shown in preclinical rodent models to modulate cerebral cortex excitability 7 and improve postischemia motor recovery. 106 More recently, chronic cerebellar DBS demonstrated promotion of long-term potentiation, neuroplasticity, and reparative reorganization.…”
Section: Cerebellar Stimulationmentioning
confidence: 99%
“…One of the possible mechanisms underlying the effects of DTC pathway stimulation on motor recovery and perilesional plasticity is via modulation of cortical excitability and reversal of crossed cerebellar diaschisis [10]. We have recently shown that chronic stimulation of the LCN increases cortical excitability over sustained periods of time in naïve animals, in a frequency-specific fashion [17]. Further, we have shown previously that despite phase-specific interactions with anesthetic agents, the enhanced cortical excitability by LCN stimulation is robust and reproducible in naïve animals [18].…”
Section: Introductionmentioning
confidence: 99%
“…By targeting it at its node of origin in the dentate nucleus or the ascending pathway, the majority of the tract can be activated with a single implanted multipolar electrode [69]. Invasive, subthreshold stimulation, delivered chronically at lower frequencies (in the beta range) can generate sustained facilitatory effects upon excitability of M1 [70] and promote recovery of the impaired forelimb to a significantly greater degree than in a control [71,72].…”
Section: Methodological: Targeting Peri-lesional Substrates Even Whilmentioning
confidence: 99%